Investigação biotécnica de espécies com potencial de uso em obras de engenharia natural - Kettenhuber, Paula Letícia Wolff (2017)
Plants are considered as an important structural component of Soil Bioengineering interventions and their use as live construction material requires an adequate selection of the species to be used, constituting a determining factor for the success of the interventions. The selected species must possess biotechnical properties, considering also some requirements, namely the edaphoclimatic, ecological and reproduction aspects of the species. Vegetative propagation is the preferred form of reproduction in Soil Bioengineering and its capacity is intrinsic to each species, being influenced by several factors, especially the time of year of collection and planting. The present study aims to investigate the vegetative propagation by cuttings and the biotechnical properties of the species Allamanda cathartica L., Cephalanthus glabratus (Spreng.) K. Schum., Escallonia bifida Link & Otto, Ludwigia elegans (Camb.) H. Hara, Sambucus australis Cham. & Schltdl., Sesbania virgata (Cav.) Pers. e Terminalia australis Camb., in order to subsidize the selection and appropriate use of these species in Soil Bioengineering interventions. Two different methodologies were used, the first was the conduction of an automated greenhouse experiment at the Laboratory of the Soil Bioengineering of Federal University of Santa Maria, at two period of the year (autumn/winter and late winter/spring). In which hardwood cuttings of 20 cm in length of the seven species were planted in pots filled with medium sand. Completely randomized experimental arrangement was used with 60 cuttings for each species and at each period of the year. After 90 days, the following variables were evaluated: survival and rooting rate, mean number and sum of shoot length per plant, mean number and sum of the length of primary roots per plant, mean dry shoot and root mass, number of roots and sum of root length per meter of buried cutting. The second methodology adopted was to perform anatomical studies from cuttings samples from the previous experiment of the seven species to verify the existence of anatomical barriers to rooting and to describe the wood in a preliminary way, as well as to perform an analysis with a view to the determination of the flexibility of their stems. The microscopic description followed the recommendations of the IAWA Committee. In the first experiment, all the species presented vegetative propagation capacity, which ranged from 23.3% to 100%. In general, the species showed better survival rates, rooting and development of the aerial part and root system at the end of the period later winter/spring. Through the anatomical analysis of the species it was possible to identify sclerenchymatic tissue in the species S. virgata, S. australis and C. glabratus. As for the flexibility of the stems, it was possible to infer that the species S. virgata, T. australis e C. glabratus probably have flexible branches. The results indicate the biotechnical potential of L. elegans, S. virgata, C. glabratus and A. cathartica, being able to print rhythm of development of the root system and expected aerial part in Soil Bioengineering works. T. australis, E. bifida and S. australis presented vegetative propagation capacity, but slower rooting, and can be used when there is interest in increasing species diversity.